The level of expertise of the students of the Department of Family Education and the technical professions and their applications in primary schools (Journal of the College of Basic Education, 2020)
The aim of the current research is to determine the level of expertise of the students of the Department of Family Education and the technical professions and their applications in primary schools. To determine the level of expertise and its applications in the primary schools, the researcher constructed a questionnaire consisting of two fields: the first is the theoretical experience, the second is the administrative expertise, The researcher applied the questionnaire to a sample of the students of the Department of Family Education and Technical professions numbering (30) students and students. After collecting the information and data, the researcher reached the following results:1-The level of experience is good for the applied students 2-There is a weakness in the level of administrative experience for students appliedBased on the results of the research, the researcher came out with a set of recommendations and suggestions